Studi Pemanfaatan Pekarangan Rumah Terkait Tumbuhan Obat Keluarga (Toga) Di Desa Bubulak RW 06 Bogor - Julian Dwi Novaldi; Ninuk Purnaningsih (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
An Issue about food hunger security is still existing nowadays in Indonesia. Human population growth & cropping ground conversion are the major factors that caused food hunger security. One potential of Medical Herb Plant (TOGA) mostly was ignored by people, in other side it’s become solution to fight back the food security issue and need some support from government for land & yard usage in every house. Beneficial of TOGA are to counter food hunger security, support family health & curing a light to serious illness, reducing family allowance and increasing family finances. This study held in RW 06 Bubulak’s village, Sub-district West Bogor, Bogor City for two weeks & belongs to SUIJI-SLP 2019. The data of this study were obtained from community interviews and field observation. This study also aimed to knowing the condition of yard usage for Medical Plant Herb (TOGA) by villager. RW 06 had five people that have knowledge about TOGA in their yard. To conclude this study, TOGA program has a dual function including beautifying homes, sources of natural medicinal herbs and herbs, increasing family financial income, and increasing harmony among residents. This TOGA program planning in RW 06 Bubulak’s village was considered to have some potential to be develop need participation from villager and some support from government too. It’s relating the needed for elucidation and TOGA’s cadre establishment. Key words: empowerment for land yard, independent & healty family, TOGA conservation